Uporaba numeričnih simuliranj pri razvoju orodij za izdelavo pločevinastih sestavnih delov avtomobilov - Gantar, Gašper (Strojniški vestnik, 2001)
Many tool-manufacturing companies in Slovenia are producing the tools required for the sheet-metal parts of cars. Numerical simulations based on the finite-element method (FEM) have recently become widely used in order to reduce the development times and the number of mistakes associated with the manufacture of these tools. Production technologies are tested in the so-called virtual environment before the tools are produced. Mistakes are detected at an early phase of the development cycle, and as a result, their removal is cost effective. In this paper we present the implementation of numerical simulations in the development cycle of a tool for a new product.
Keywords: preoblikovanje pločevine; simuliranje numerično; razvoj izdelkov; optimiranje; automotive industry; avtomobilska industrija; orodje; razvoj; numerična simulacija; preoblikovanje